Developing Phenomenological Method for Researching Lesbian Existence - Hunnisett, Rowena J. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper argues a complementary relationship between phenomenological method and feminist theory; then develops a research method suited to the study of lesbians in their communities. A comparison of three phenomenological methods produces one new method with methodological innovations in interviewing, mapping and data analysis. Findings of the study under discussion are summarized. Pitfalls and challenges of phenomenological research, and implications for counsellors and researchers are outlined.